Occurrence of Philornis bella Couri in nestlings of Tyrannus melancholicus Vieillot (Tyranninae) in the municipal district of Seropédica, Rio de Janeiro - Hermes Ribeiro Luz; Bruno Pereira Berto; Ildemar Fereira; Rafaela Dias Antonini; André Felippe Nunes-Freitas; Gonzalo Efrain Moya Borja (Biotemas, 2011)
Five nestlings of Tyrannus melancholicus Vieillot, 1819, between nine (n = 2) and twelve days (n = 3) old, were studied from July to September in 2006. A total of 43 larvae was collected, of which 33 (76%) became adults and were identified as Philornis bella Couri, 1984. The most infested areas of the nestlings were the wings (44%), head (39.5%) and coxae (16.5%). None of the nestlings died during the study. This is the first record of P. bella parasitizing nestlings of Tyrannus melancholicus.